Incidence and risk factors of neurological deficits of surgical correction for scoliosis: analysis of 1373 cases at one Chinese institution - Qiu, Yong; Wang, Shoufeng; Wang, Bin; Yu, Yang; Zhu, Feng; Zhu, Zezhang (Spine (Philadelphia, Pa. 1976), 2008)
A retrospective study. To investigate the incidence of neurologic deficits after scoliosis correction at 1 institution and identify the risk factors for such deficits in scoliosis correction. Neurologic deficit is one of the risks of surgical correction of scoliosis. Reports of the incidence of the neurologic deficits involving a large number of cases at 1 institution are rare. Statistical analysis of the neurologic deficits was performed in 1373 scoliosis cases treated at 1 institution by etiologies in light of the patients' sex, age, sagittal profile, surgical approach, Cobb's angle, and the type of surgery. The total incidence of neurologic deficits was 1.89% and that of serious and mild ones was 0.51% and 1.38%, respectively. The total incidence of neurologic deficits were 1.06% in adolescent idiopathic scoliosis patients and 2.89% in congenital scoliosis (CS) patients, 3.32% in scoliosis patients with hyperkyphosis (>40 degrees ) and 1.38% in those without hyperkyphosis, 3.43% for combined procedures and 1.24% for single posterior procedures, 3.69% in patients with Cobb's angle more than 90 degrees and 1.45% in those with an angle less than 90 degrees , 1.68% with primary surgery and 5.97% with revision surgery, the difference between them was significant (P < 0.05). In adolescent idiopathic scoliosis patients, the incidence were 3.85% for combined procedures and 0.64% for posterior procedure, 0.82% with primary surgery and 8.33% with revision surgery, 4.17% with hyperkyphosis and 0.61% without hyperkyphosis, the difference between them was significant (P < 0.05). The incidence of CS patients with Cobb's angle more or less than 90 degrees were 7.23% and 1.68% and the difference was significant (P < 0.05). In surgical correction of scoliosis, the risk factors for neurologic deficits include CS, scoliosis with hyperkyphosis, scoliosis correction by combined procedures, scoliosis with a Cobb's angle more than 90 degrees , and a revision surgery.